ABVD vs BEACOPP escalated in advanced‐stage Hodgkin's lymphoma: Results from a multicenter European study. Issue 9 (30th June 2020) - Mondello, Patrizia; Musolino, Caterina; Dogliotti, Irene; Bohn, Jan‐Paul; Cavallo, Federica; Ferrero, Simone; Botto, Barbara; Cerchione, Claudio; Nappi, Davide; De Lorenzo, Sonya; Martinelli, Giovanni; Wolf, Dominik; et al.
Abstract: The optimal first‐line treatment for advanced‐stage Hodgkin's lymphoma (HL) is still a matter of debate. While ABVD is less toxic and as effective as other, more intensive chemotherapy regimens, escalated BEACOPP (BEACOPPesc) is superior to ABVD for initial disease control and prolonged time‐to‐relapse. However, this advantage is associated with higher rate of early and late toxicities. As most of these data have been accumulated from clinical trials, a retrospective analysis was conducted in a large database of patients treated outside clinical trials to investigate the advantages and disadvantages of these regimes in a real‐world setting. From October 2009 to October 2018, 397 advanced‐stage HL patients treated with either ABVD or BEACOPPesc were retrospectively assessed in 7 European cancer centers (2 Austrian and 5 Italian centers). Complete metabolic remission (CMR) by PET was achieved in 76% and 85% of patients in the ABVD and BEACOPPesc groups, respectively ( p  = .01). Severe adverse events occurred more frequently with BEACOPPesc than ABVD. At a median follow‐up of 8 years, 9% of the patients who achieved CMR after BEACOPPesc relapsed compared to 16.6% in the ABVD group ( p = .043). No statistical difference in progression free survival (PFS) was observed between the two cohorts overall ( p = .11), but there was a trend towards a superior PFS in high‐risk patients treated with BEACOPPesc ( p = .074). Nevertheless, overall survival was similar between the two groups ( p = .94). In conclusion, we confirm that ABVD is an effective and less toxic therapeutic option for advanced‐stage HL. Although BEACOPP results in better initial tumor control, the long‐term outcome remains similar between the two regimens.